Misleading Tax Figures–A Problem for Accountants: A Reply. - Weber, Richard P. (The Accounting Review, 1978)
Abstract The article presents the author's reply to comments on his paper "Misleading Tax Figures–A Problem for Accountants." According to the author, ideally, a single, theoretically defensible allocation formula would be prescribed for financial reporting. This method might be incorporated into the tax law. This does not suggest that allocation methods used for tax purposes should conform to GAAP. It was commented that where a consolidated tax liability is allocated for tax purposes in one way, but actual payment reflects a different allocation, the one which is used for payment purposes determine basis. This determination is unclear to the author. Presumably, the commentator is referring to payments among affiliates pursuant to the agent corporation paying the consolidated tax. The commentator seems to be saying that the allocation is ignored when it differs from the payment where both the allocation and payment arise from the group's consolidated tax liability. The commentator correctly observes that where a subsidiary is to be sold, the parent will generally try to minimize the taxable gain on the sale by maximizing its basis in the subsidiary.